Editorial (Intervention. European Journal of Economics and Economic Policies, 2011)
The crisis of the euro area has become increasingly virulent over recent months. The very existence of the common currency is at risk, and the lack of determination especially of the German government in terms of European solidarity causes widespread fears of a collapse of the monetary union and might lead to a severe backlash against the process of European integration as a whole. The Forum section therefore contains two articles by Torsten Niechoj and Till van Treeck and by Karl Betz providing background analyses of the crisis. Although in the public debate the current crisis is still widely considered to be primarily a public debt crisis the authors point at the structural, macroeconomic causes of the crisis, with special emphasis on external trade and current account imbalances. The Forum section is completed by an interview conducted with Stephen Marglin.
Keywords: 330